ChemInform Abstract: Palladium‐Catalyzed Cross‐Coupling Reactions of Triarylbismuthanes with Terminal Alkynes under Aerobic Conditions. Issue 1 (17th December 2015) - Matsumura, Mio; Yamada, Mizuki; Tsuji, Toshiyuki; Murata, Yuki; Kakusawa, Naoki; Yasuike, Shuji
Abstract: A novel and mild Sonogashira‐coupling reaction with triarylbismuthanes under aerobic conditions is presented.